Research Advances on Quality Evaluation Factors and Preservation Technology of Edible Mushrooms - Kecheng RAO; Wen HUANG; Yi WANG; Defang SHI; Hong GAO; Ying LIU (Shipin gongye ke-ji, 2023)
Edible mushrooms are well received by consumers due to their various nutrients and tasty. However, mushrooms are prone to cap opening, browning, rotten and other deterioration phenomena after harvest, which severely limits the development of mushrooms industry. Therefore,this paper summarizes the quality evaluation factors of mushrooms, including sensory quality, intrinsic quality and safety. As an example, the preservation technologies of Agaricus bisporus are summarized, including physical preservation (low temperature preservation, modified atmosphere preservation, radiation preservation, dehydration treatment preservation, magnetic field preservation and electrostatic field preservation), chemical preservation (chemical preservatives preservation, ozone preservation, electrolyzed water and plasma-activated water preservation) and biological preservation (biological coating preservation, plant extracts preservation, microbial preservatives preservation and antagonistic bacteria preservation). The application of preservation technologies in mushrooms is also summarized. The shortcomings in the current quality evaluation and preservation technologies of mushrooms are put forward. The development of the quality evaluation and preservation of mushrooms is prospected in order to promote the progress and development of mushrooms industry in the future.